Identification and characterisation of microsatellite markers in narrow barred Spanish mackerel Scomberomorous commerson (Lacepede, 1800) - Divya, P. R.; Vineesh, N.; Kathirvelpandian, A.; Mohitha, C.; Basheer, V. S.; Gopalakrishnan, A.; Jena, J. K. (Indian Journal of Fisheries, 2016)
Narrow barred Spanish mackerel, Scomberomorus commerson (Lacepede 1800) is one of the commercially important fish in Indian waters. For sustainable management of the species, it is necessary to understand the genetic stock structure of the species. Accurate delineation of genetic stock structure can be achieved using nuclear microsatellite markers. A study was carried out to identify and validate polymorphic microsatellite markers in S. commerson using information available from closely related fish species. The study could identify 10 polymorphic microsatellite loci which can be effectively utilised for identifying genetic stock structure of the species. Validation of the identified loci was also done by testing the loci in natural populations of the species. The findings of the present study will be useful in devising stock-specific management measures for conservation and sustainable utilisation of this commercially important fish species in Indian waters.